IDENTIFICATION OF URINARY INCONTINENCE IN PEOPLE AGED 65 AND OVER: A TURKEY SAMPLE - Birsel Canan Demirbag; Gulpinar Aslan; Ayse Berivan Bakan (Belitung Nursing Journal, 2017)
Objective: This study aims to identify urinary incontinence and its prevalence in people aged 65 and over. Methods: This descriptive study was conducted between April and June, 2017. It was conducted with 1527 volunteer people aged 65 and over who applied to A Family Health Centre. Data were collected through face-to-face interviews, using Personal Identification Form and International Consultation on Incontinence Questionnaire- Short Form (ICIQ-SF). Results: Of all the participants, 50.7% were male, and 78.8% were aged between 65 and 74. Besides, 31.2% of them had urinary incontinence, and ICIQ-SF mean score was found 11.44 ± 5.01. The most prevalent incontinence type was found to be urge urinary incontinence. ICIQ-SF total scores of elderly people with urinary incontinence were higher in those who were aged 85 and over, who were illiterate, who did not have health insurance, and who had more than one chronic disease and multiple medicine use. Conclusion: Urinary incontinence is a health problem which maintains its importance in people aged 65 and over. People in this age group do not express this problem because they feel shy; therefore, their quality of life deteriorates.